Pemahaman dan Tantangan Kepatuhan Pajak pada Pelaku UMKM di Provinsi Daerah Istimewa Yogyakarta - Raden Alem Janitra Abdul Rahman (Lembaga Teewan Journal Solutions, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy yet continue to face various obstacles in meeting their tax obligations. This study aims to analyze the factors influencing the tax understanding and compliance of MSME operators in the Special Region of Yogyakarta, focusing on the mindsets underlying their tax-related decision-making. The research employs a qualitative approach grounded in the phenomenological-interpretivist paradigm. Data were gathered through semi-structured interviews with nine MSME owners or managers—selected via purposive sampling—and analyzed using thematic analysis. The findings indicate that tax compliance is driven more by concerns regarding administrative sanctions and legal consequences than by moral awareness. Key barriers include low tax literacy, regulatory complexity, limited access to information, and the high cost of professional assistance. Furthermore, perceptions of an unfair tax system, poor public service quality, and declining trust in the government also play a role. These findings underscore the importance of simplifying regulations, strengthening tax education, and enhancing transparent governance to foster voluntary compliance among MSME operators.